2018
DOI: 10.3892/etm.2018.5901
|View full text |Cite
|
Sign up to set email alerts
|

Tripterygium�wilfordii mitigates hyperglycemia-induced upregulated Wnt/β-catenin expression and kidney injury in diabetic rats

Abstract: Aberrant activation of the Wnt/β-catenin pathway contributes to the development of diabetic nephropathy (DN); however, treatment with Tripterygium wilfordii (TW) may be beneficial for patients with DN. The aim of the present study was to evaluate the effect of TW on Wnt/β-catenin expression in the kidneys of diabetic rats. Male Sprague-Dawley rats were randomly injected with vehicle (control) or streptozotocin to induce diabetes. Diabetic rats were then randomly treated with vehicle (sodium carboxymethyl cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Wnt/β-catenin signaling is an evolutionary conserved signaling pathway, which plays a core role in modulating kidney injury and repair ( 114 ). In DN rats, Chang et al drew a conclusion that TWHF mitigates hyperglycemia-induced upregulated Wnt-1 and β-catenin expression in kidney tissues and ameliorates kidney injury ( 67 ) ( Table 1 , Figures 2 , 3 ).…”
Section: Other Effects Of Twhf and Its Main Bioactive Ingredientsmentioning
confidence: 99%
“…Wnt/β-catenin signaling is an evolutionary conserved signaling pathway, which plays a core role in modulating kidney injury and repair ( 114 ). In DN rats, Chang et al drew a conclusion that TWHF mitigates hyperglycemia-induced upregulated Wnt-1 and β-catenin expression in kidney tissues and ameliorates kidney injury ( 67 ) ( Table 1 , Figures 2 , 3 ).…”
Section: Other Effects Of Twhf and Its Main Bioactive Ingredientsmentioning
confidence: 99%
“… 6 , 7 Many results have shown that TGF-β expression is upregulated in animal renal fibrosis models as well as human counterparts. 8 , 9 The transition of renal tubular epithelial cells to myofibroblasts which synthesize excessive amounts of extracellular matrix thus leading to renal fibrosis is modulated by TGF-β through TGF-β/Smads signaling pathway. 2 Furthermore, oxidative stress and TGF-β/Smads signaling together with other disease processes interactively and rapidly promote DN.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, serum and urine levels of the EMT markers MMP-2 and -9 and E-cadherin were found to be elevated in CKD children [13]. Expression of interstitial cell markers has also been observed in the renal tubules of patients with diabetic nephropathy [14], lupus nephritis [15], oligoimmune complex type crescentic glomerulonephritis [16], IgA nephropathy [17], and chronic allograft nephropathy [18]. Thus, renal tubular EMT is an important mechanism of renal fibrosis and progression.…”
Section: Discussionmentioning
confidence: 99%